1998
DOI: 10.1590/s0006-87051998000200005
|View full text |Cite
|
Sign up to set email alerts
|

Análise Dialélica De Seis Características Agronômicas Em Phaseolus Vulgaris L.

Abstract: Os cultivares de feijão-de-vagem Alessa, Hab 52 e Hab 198, as linhagens de feijão comum Bac-6 e A-794 e os dez possíveis híbridos F1s dialélicos foram avaliados quanto ao número de vagens e de sementes por planta, comprimento, diâmetro e teor de fibra da vagem e altura de planta. A análise dialélica foi feita com base no método II, modelo 1 de Griffing. A capacidade geral de combinação foi significativa para todos os caracteres avaliados. Efeitos significativos para a capacidade específica de combinação foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 3 publications
0
7
0
2
Order By: Relevance
“…These results suggest that the heterotic effects detected in F 2 are small. The predominance of dominance effects associated with grain yield in common bean was reported by Rodrigues et al (1998) and Gonçalves-Vidigal et al (2008). However, other studies reported predominantly additive effects for YLD (Santos et al 1985, Kurek et al 2001).…”
Section: Resultsmentioning
confidence: 94%
“…These results suggest that the heterotic effects detected in F 2 are small. The predominance of dominance effects associated with grain yield in common bean was reported by Rodrigues et al (1998) and Gonçalves-Vidigal et al (2008). However, other studies reported predominantly additive effects for YLD (Santos et al 1985, Kurek et al 2001).…”
Section: Resultsmentioning
confidence: 94%
“…Rodrigues et al (1998), por exemplo, na análise dos efeitos gênicos atuantes em dialelo envolvendo cinco genitores de hábito determinado, detectaram que os efeitos de dominância foram preponderantes para altura de planta. Por sua vez, Leal et al (1979), utilizaram a potencialidade do dialelo parcial em feijão-de-vagem, para 1/ nmv =número médio de vagens por planta; PMV = peso médio de vagens por planta; NS = número médio de sementes por vagem; APV = altura média da inserção da primeira vagem; CV = comprimento médio da vagem investigar os efeitos gênicos sobre características de produção, pela comparação entre a performance de gerações F 5 e F 6 , em relação a F 1 e F 2 , tendo concluído que a aditividade, e também a epistasia, foram predominantes, apesar de haver sido detectadas diferenças entre os genitores dependendo da característica e do ano avaliado.…”
Section: Resultsunclassified
“…It is worth mentioning that works approaching diallel analysis in snap beans are unusual, having, among those few studies, divergence regarding results achieved. Rodrigues et al (1998), when analyzing the genic effects in diallel, showed that the dominance effects were predominant for plant height. In turn, when Leal et al (1979) applied the potential of the partial diallel in the snap bean to evaluate the genic effects on the yield trait, they inferred that the additivity and the epistasis were predominant.…”
Section: Sources Of Variation Dfmentioning
confidence: 99%